HUBUNGAN KESEJAHTERAAN SPIRITUAL DAN KUALITAS HIDUP PADA PASIEN HIPERTENSI - Yenni Yenni; Suharwi Suharwi; Dini Qurrata Ayuni; Rola Oktorina (Ensiklopedia Research and Community Service Review, 2026)
Abstract: Hypertension is a leading cause of premature death worldwide and requires optimal management to maintain quality of life and prevent cardiovascular complications. Spiritual well-being is one of the factors influencing the quality of life of hypertensive patients. This study aimed to analyze the relationship between spiritual well-being and quality of life among hypertensive patients at the Tanjung Enim Community Health Center. An analytical study with a cross-sectional design was conducted involving 60 hypertensive patients selected via accidental sampling. Data analysis was performed using Fisher’s Exact test. The results showed that 78.3% of respondents had a poor quality of life, and 85.0% had poor spiritual well-being. Statistical analysis yielded a p-value of 0.018 (p ≤ 0.05), indicating a significant relationship between spiritual well-being and quality of life. It is concluded that poor spiritual well-being is associated with poor quality of life in hypertensive patients. Healthcare providers are encouraged to develop services that address patients' spiritual needs to improve their quality of life.Keywords: Hypertension, Spiritual Well-Being, Quality Of Life, Hypertensive Patients